The relationship between nurse contact time and patient outcomes: a retrospective observational study using Real-Time Location data - Elena Ashtari Tafti; Ann-Marie Cannaby; Vanda Carter; Stephenson Strobel (BMC Health Services Research)
Abstract In this study, we utilize a novel and unique data source to examine the relationship between nurses’ contact time and patients’ hospital outcomes. While previous research has demonstrated that higher nurse staffing levels lead to better outcomes, the specific contribution of increased direct patient care time to these improvements remains unknown. Using data from a Real-Time Location System (RTLS) that tracks the movement of staff and patients across the hospital wards using Global Positioning System (GPS) sensors, we can estimate the time patients “actually” spend with nursing staff during an inpatient stay. We find that the average patient is in contact with nurses for about 8 h a day, of which 22 min are of direct care at the patient’s bedside. We find a statistically significant association between contact time, measured as the total number of minutes in a day the patient is in contact with nursing staff, and in-hospital mortality. A 10-minute increase in contact time is associated in our data with a 0.05% reduction in mortality. By emphasizing the importance of patient-centered care and the role of contact time in shaping patient outcomes, our results suggest the need for healthcare institutions to prioritize strategies that optimize patient-provider interactions.